(3LhGgQ GdJQUjY aj Yde GdHOjYs - (3YHO GdYRjR Hf SQGjG Hf Ydj Hf CHj GdbGSe GdSfHSj GdWGFj GdMdj , Uaj GdOjf,J (B750 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Qbe Mdg GdEYLGR CeG HYO aEfi deG QCjJ HdZGA gPg GdCeI ef GdTYQGA hGdCFeI s
(3BNQgG (B:s
(3hdPdc GdfUa GdCNQ ef GdHjJ aEfg GdfUa GdCNQ ef GdHjJ aEfg GdfUa GdChd ef GdHjJ GdChd efgG hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B6s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdYHGSjI (B- (3NRGfI Bd HGTf CYjGf GdHUQI (B(26 (3C(B) s
Keywords: (3GdeLGejYs